The magnetic ground state of two isostructual polymeric quantum magnets, [Cu(HF2)(pyrazine)SbF6 and [Co(HF2)(pyrazine)2]SbF6, investigated with neutron powder diffraction - Brambleby, J; Goddard, P; Johnson, R; Liu, J; Kaminski, D; Ardavan, A; Steele, A; Lancaster, T; Manuel, P; Baker, P; Singleton, J; Schwalbe, S; et al. (American Physical Society, 2015)
The magnetic ground state of two isostructural coordination polymers (i) the quasi two-dimensional S = 1/2 square-lattice antiferromagnet [Cu(HF$_{2}$)(pyrazine)$_{2}$]SbF$_{6}$; and (ii) a new compound [Co(HF$_{2}$)(pyrazine)$_{2}$]SbF$_{6}$, were examined with neutron powder diffraction measurements. We find the ordered moments of the Heisenberg S = 1/2 Cu(II) ions in [Cu(HF$_{2}$)(pyrazine)$_{2}$]SbF$_{6}$ are 0.6(1)$μ_{B}$, whilst the ordered moments for the Co(II) ions in [Co(HF$_{2}$)(pyrazine)$_{2}$]SbF$_{6}$ are 3.02(6)$μ_{B}$. For Cu(II), this reduced moment indicates the presence of quantum fluctuations below the ordering temperature. We show from heat capacity and electron spin resonance measurements, that due to the crystal electric field splitting of the S = 3/2 Co(II) ions in [Co(HF$_{2}$)(pyrazine)$_{2}$]SbF$_{6}$, this isostructual polymer also behaves as an effective spin-half magnet at low temperatures. The Co moments in [Co(HF$_{2}$)(pyrazine)$_{2}$]SbF$_{6}$ show strong easy-axis anisotropy, neutron diffraction data which do not support the presence of quantum fluctuations in the ground state and heat capacity data which are consistent with 2D or close to 3D spatial exchange anisotropy.